Ius Constituendum Urun Dana untuk Badan Usaha Non-Badan Hukum - Muhammad Asrul Maulana; Gabriella Novena Winarta (Jurnal Hukum Positum, 2025)
The development of crowdfunding in Indonesia presents legal challenges related to organizer regulations that do not comply with existing provisions, especially for non-legal entities such as social communities, maatschap, or faith-based organizations. Financial Services Authority Regulation No. 57/POJK.04/2020 requires crowdfunding organizers to be established as Indonesian legal entities such as Limited Liability Companies (PT) or cooperatives. However, many crowdfunding practices are carried out by non-formal entities that are not legally recognized, creating a legal vacuum that has the potential to lead to legal uncertainty, misuse of funds, and violations of investor rights. This article proposes the importance of ius constituendum to regulate non-legal entities in crowdfunding activities, with an approach that is more responsive to social and technological dynamics. More flexible regulations are needed to align socio-economic practices with the existing legal system, thereby creating a fair and inclusive legal environment for all forms of crowdfunding activities.